A focus on the preclinical development and clinical status of the histone deacetylase inhibitor, romidepsin (depsipeptide, Istodax®). (October 2012) - Harrison, Simon J; Bishton, Mark; Bates, Susan E; Grant, Steven; Piekarz, Richard L; Johnstone, Ricky W; Dai, Yun; Lee, Becki; Araujo, Maria E; Prince, H Miles
Romidepsin (Istodax ®, depsipeptide, FR901228, FK228, NSC 630176) is a cyclic peptide, broad-spectrum, potent histone deacetylase inhibitor, with activity mainly against class I histone deacetylase enzymes. In this article, we give an overview of the putative modes of action, such as effects on gene expression, cell cycle regulation, apoptosis induction, DNA repair, protein acetylation and induction of autophagy. Romidepsin has mainly been developed as a therapy for hematologic malignancies and is approved by the US FDA for the treatment of cutaneous T-cell lymphomas. This report outlines the laboratory and clinical development of the compound as a single agent that has more recently been evaluated in combination with other anticancer therapeutics, such as proteasome inhibitors.